An innovative thermodynamic model for performance evaluation of photovoltaic systems: Effect of wind speed and cell temperature. (15th March 2017) - Kaushik, S.C.; Rawat, Rahul; Manikandan, S.
Highlights: A novel thermodynamic modelling of photovoltaic energy system has been proposed. The entropy, optical, thermal, spectral and fill factor losses are assessed. The expression of energetic and exergetic efficiencies have been derived. Reversible, endoreversible, exoreversible and irreversible systems are presented. Abstract: The photovoltaic energy conversion is a thermodynamic system which converts the solar energy to the electrical and thermal energy. In this paper, a novel thermodynamic model of photovoltaic energy conversion system has been proposed on the basis of the first and second law of thermodynamics including entropy generation, optical, thermal, spectral and fill factor losses. Based on the irreversibilities, the proposed model has been classified into four cases i.e. reversible, endoreversible, exoreversible and irreversible systems, for which, the expressions of energetic and exergetic efficiencies have been derived. The upper limit efficiency of an ideal photovoltaic module placed in an irreversible environment, i.e. endoreversible system, is determined to be 82.8%. The effect of wind speed and module temperature on the energetic and exergetic efficiencies, thermodynamic losses and irreversibilities has also been presented.